Using a noninfectious MVM surrogate for assessing viral clearance during downstream process development. (14th October 2019) - Orchard, Joshua D.; Cetlin, David; Pallansch, Melanie; Barlow, Robert; Borman, Jon; Dhar, Arun; Pallansch, Luke; Dickson, Matthew
Abstract: Viral contamination is an inherent risk during the manufacture of biopharmaceuticals. As such, biopharmaceutical companies must demonstrate the viral clearance efficacy of their downstream process steps prior to clinical trials and commercial approval. This is accomplished through expensive and logistically challenging spiking studies, which utilize live mammalian viruses. These hurdles deter companies from analyzing viral clearance during process development and characterization. We utilized a noninfectious minute virus of mice‐mock virus particle (MVM‐MVP) as a surrogate spiking agent during small scale viral filtration (VF) and anion exchange chromatography (AEX) studies. For VF experiments, in‐process mAb material was spiked and processed through Asahi Kasei P15, P20, P35, and BioEX nanofilters. Across each filter type, flux decay profiles and log reduction values (LRVs) were nearly identical for either particle. For AEX experiments, loads were conditioned with various amounts of sodium chloride (9, 20, 23, and 41 mS/cm), spiked with either particle and processed through a Q‐SFF packed column. LRV results met our expectations of predicting MVM removal.